2009
DOI: 10.1002/dvdy.21848
|View full text |Cite
|
Sign up to set email alerts
|

Acheate‐scute like 1 (Ascl1) is required for normal delta‐like (Dll) gene expression and notch signaling during retinal development

Abstract: Delta gene expression in Drosophila is regulated by proneural basic helix-loop-helix (bHLH) transcription factors, such as acheate-scute. In vertebrates, multiple Delta-like and proneural bHLH genes are expressed during neurogenesis, especially in the retina. We recently uncovered a relationship between Acheate-scute like 1 (Ascl1), Delta-like genes, and Notch in chick retinal progenitors. Here, we report that mammalian retinal progenitors are also the primary source of Delta-like genes, likely signaling throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 90 publications
3
81
0
Order By: Relevance
“…Ascl1 impacts Notch signaling during retina development by regulating the expression of genes encoding Notch ligands (Nelson et al, 2009; Nelson and Reh, 2008). Notch signaling components are also induced in the injured adult zebrafish retina (Raymond et al, 2006; Yurco and Cameron, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascl1 impacts Notch signaling during retina development by regulating the expression of genes encoding Notch ligands (Nelson et al, 2009; Nelson and Reh, 2008). Notch signaling components are also induced in the injured adult zebrafish retina (Raymond et al, 2006; Yurco and Cameron, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an Ascl1a/Delta/Notch molecular circuitry maintains retinal progenitors during development of the mammalian retina (Nelson et al, 2009) and Notch signaling components are re-activated during zebrafish retina regeneration (Raymond et al, 2006; Yurco and Cameron, 2007). However, it is not clear if Ascl1a mediates Notch signaling component gene induction in the injured retina.…”
Section: Introductionmentioning
confidence: 99%
“…TPCs express high levels of neuroendocrine differentiation compared to non-TPCs, including Ascl1 , a key oncogenic factor in SCLC (Augustyn et al, 2014; Jiang et al, 2009). Accordingly, treatment with a drug-conjugated antibody against DLL3, a transcriptional, target of ASCL1 (Nelson et al, 2009), was shown to inhibit the transplantation ability in human SCLC PDX models (Saunders et al, 2015). We focused on MYC based on its known oncogenic role in SCLC (Alves Rde et al, 2014; Calbo et al, 2005; George et al, 2015; Huijbers et al, 2014; Romero et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…dla , dlc and n1a are expressed in a graded fashion along the apical-basal axis within the zebrafish retinal neuroepithelium and this graded localization is thought to dictate the level of Notch signaling a retinoblast is exposed to during interkinetic nuclear migration (IKNM) (Del Bene et al, 2008). Dll1 , orthologous to zebrafish dla , is expressed in chicken retinoblasts (Nelson and Reh, 2008; Nelson et al, 2009), and its ectopic expression prevents retinal progenitor cells from differentiating (Henrique et al, 1997). Regulated expression of each of these factors is therefore critical to control the balance between proliferation and differentiation in retinoblasts, and this balance is disrupted in Id2a-deficient retinae.…”
Section: Discussionmentioning
confidence: 99%
“…Id2 can bind to and sequester E12 and E47 proteins in fibroblasts, thereby modulating the expression of cell cycle regulators, indicating that Id2 has the capacity to inhibit E2A heterocomplex formation (Trabosh et al, 2009). Id2a could also sequester the bHLH protein Ascl1a, a Notch pathway target gene itself, which functions to activate the expression of delta-like and other Notch pathway targets in the retina (Nelson et al, 2009). Indeed, numerous factors have been shown to regulate Notch pathway gene expression, both transcriptionally and post-transcriptionally, and may of these also represent possible candidates for Id2a antagonism.…”
Section: Discussionmentioning
confidence: 99%